Metabolic vulnerability of cisplatin‐resistant cancers. (6th June 2018) - Obrist, Florine; Michels, Judith; Durand, Sylvere; Chery, Alexis; Pol, Jonathan; Levesque, Sarah; Joseph, Adrien; Astesana, Valentina; Pietrocola, Federico; Wu, Gen Sheng; Castedo, Maria; Kroemer, Guido
Abstract: Cisplatin is the most widely used chemotherapeutic agent, and resistance of neoplastic cells against this cytoxicant poses a major problem in clinical oncology. Here, we explored potential metabolic vulnerabilities of cisplatin‐resistant non‐small human cell lung cancer and ovarian cancer cell lines. Cisplatin‐resistant clones were more sensitive to killing by nutrient deprivation in vitro and in vivo than their parental cisplatin‐sensitive controls. The susceptibility of cisplatin‐resistant cells to starvation could be explained by a particularly strong dependence on glutamine. Glutamine depletion was sufficient to restore cisplatin responses of initially cisplatin‐resistant clones, and glutamine supplementation rescued cisplatin‐resistant clones from starvation‐induced death. Mass spectrometric metabolomics and specific interventions on glutamine metabolism revealed that, in cisplatin‐resistant cells, glutamine is mostly required for nucleotide biosynthesis rather than for anaplerotic, bioenergetic or redox reactions. As a result, cisplatin‐resistant cancers became exquisitely sensitive to treatment with antimetabolites that target nucleoside metabolism. Synopsis: Cisplatin‐resistant cancers acquire a vulnerability to nutrient depletion depending on glutamine‐fueled nucleotide biosynthesis, suggesting new opportunities for combination therapies. Cisplatin‐resistant cancer cells are sensitive to starvation in vitro and in vivo . Glutamine suppresses starvation‐induced cell death. Glutamine rescues cisplatin‐resistant cells from starvation‐induced death by elevating the intracellular concentrations of nucleosides. Cisplatin‐resistant cells become exclusively sensitive to antimetabolites targeting nucleotide biosynthesis. Abstract : Cisplatin‐resistant cancers are exquisitely sensitive to starvation due to strong dependence on glutamine and nucleotide metabolism.